2019
DOI: 10.1063/1.5095619
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy characterization of neutron irradiated thermoelectric modules for space nuclear power

Abstract: The European Space Agency is currently supporting the research and development of advanced radioisotope power systems utilising thermoelectric modules. The performance of thermoelectric modules following exposure to neutron radiation is of significant interest due to the likely application of radioisotope thermoelectric generators in deep space exploration or planetary landers requiring prolonged periods of operation. This study utilises impedance spectroscopy to characterise the effects of neutron irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Mesalam et al have demonstrated, through 10 000 hours of vacuum testing, that RTG systems incorporating these Bi 2 Te 3 -based modules are relatively unaffected by changes over time. 22,23 The test results indicate an annual efficiency degradation of less than 1% for these TE converters, capable of delivering a 10 W electrical power output. Future development efforts are focused on achieving a 50 W power output using the same design principles.…”
Section: The Radioisotope Thermoelectric Generator (Rtg)mentioning
confidence: 98%
See 3 more Smart Citations
“…Mesalam et al have demonstrated, through 10 000 hours of vacuum testing, that RTG systems incorporating these Bi 2 Te 3 -based modules are relatively unaffected by changes over time. 22,23 The test results indicate an annual efficiency degradation of less than 1% for these TE converters, capable of delivering a 10 W electrical power output. Future development efforts are focused on achieving a 50 W power output using the same design principles.…”
Section: The Radioisotope Thermoelectric Generator (Rtg)mentioning
confidence: 98%
“…7 Recent advancements by the ESA have led to the development of Bi 2 Te 3 -based TE modules, specifically designed for deep-space probes using 241 Am as the fuel source. These modules operate at lower hot side temperatures than those powered by 238 Pu, 8,9,22 enabling the use of Bi 2 Te 3 -based alloys as TE materials. Traditionally, Bi 2 Te 3 alloys have seen limited use in RTGs due to their low operating temperature range of 300-600 K. However, their integration with 241 Am heat sources is highly promising.…”
Section: Thermoelectric Generator (Teg)mentioning
confidence: 99%
See 2 more Smart Citations